The Impact of General De la Rey’s Death on the Political Situation in South Africa - Michalska, Weronika (Werkwinkel, 2014)
The purpose of this article is to explain the historical significance of J.H. de la Rey’s death by analyzing the general's political involvement at the beginning of the First World War. The author also examines the outbreak of the Boer Rebellion and De la Rey's attitude towards it. The controversies surrounding the night of September 15, 1914 are discussed after providing a detailed illustration of the events leading up to the shooting the criminal activities of the Foster gang). It also analyzes the influence the general and Niklaas van Rensburg had on the Afrikaner society, which was faced with the option of revolting against the British. International media coverage of the accident is used in order to portray the world's reaction to the incident.